Monitoring of thermo-gramm at infra-red thermography and tomography; Defektoskopiya; № 2 - Vavilov V. P. Vladimir Platonovich (1992, 1992)
The paper deals with the analysis of applicability of some standard algorithms used for digital computerized image processing in active thermography and tomography. New aspects of thermal tomography are discussed taking as examples the results of studies into articles made of the acrylic plastic and carbon plastic with defects of three types (air space, polytetrafluorethylene insertion, impact injury). It is shown that the most important component of single thermogram processing is unitary or multiple smoothing spatial filtration by filters from 3×3 up to 15×15 in-size. The linear and nonlinear functions of amplitude conversion are the most efficient one among standard digital processing algorithms.